Efficacy and safety of a novel pain management device, AT-04, for endometriosis-related pain: study protocol for a phase III randomized controlled trial - Hiroshi Ishikawa; Osamu Yoshino; Fuminori Taniguchi; Tasuku Harada; Mikio Momoeda; Yutaka Osuga; Tamiki Hikake; Youko Hattori; Michiko Hanawa; Yosuke Inaba; Hideki Hanaoka; Kaori Koga (Reproductive Health, 2024)
Abstract Background Endometriosis-related pain encompassing dysmenorrhea, dyspareunia, and chronic pelvic pain, reduces the quality of life in premenopausal women. Although treatment options for endometriosis alleviate this pain, approximately one-third of women still experience pain even after receiving treatment, indicating the need for novel approaches to pain relief in those women. The Angel Touch device (AT-04) is a portable magnetic fields irradiation device that incorporates a combination of mixed alternative magnetic fields at 2 kHz and 83.3 MHz. A phase III trial confirmed the efficacy and safety of AT-02, a prototype of AT-04, for pain relief in patients with fibromyalgia. Methods This is a phase III, multicenter, prospective, randomized, sham device-controlled, double-blind, parallel study. The participants will be premenopausal women aged > 18 years who have endometriosis-related pain with at least moderate severity. Considering dropouts, 50 participants have been deemed appropriate. Eligible women will be centrally registered, and the data center will randomly allocate them in a 1:1 ratio to the intervention and control groups. Women in the intervention group will receive electromagnetic wave irradiation generated by AT-04 and those who in the control group will wear a sham device for 16 weeks, and both groups will wear AT-04 for another 4 weeks. The primary outcome measure is the change in the Numeric Rating Scale score at 16 weeks compared with the baseline. Secondary outcome measures are efficacy for pelvic pain including dysmenorrhea and non-menstrual pain, and chronic pelvic pain not related to menstruation, dysmenorrhea, and dyspareunia, and improvement of quality of life during the study period. Safety will be evaluated by device defects and the frequency of adverse events. The study protocol has been approved by the Clinical Study Review Board of Chiba University Hospital, Chiba, Japan, and will be conducted in accordance with the principles of the Declaration of Helsinki and the Japanese Clinical Trials Act and relevant notifications. Discussion This study aims to develop a novel method of managing endometriosis-related pain. The AT-04 is an ultralow-invasive device that can be used without inhibiting ovulation, suggesting potential benefits to women of reproductive-age. Trial registration number Japan Registry of Clinical Trials (jRCTs032230278).